Synthesis and Characterization of Cu(II) Substituted Hexa Tungstate and Molybdate of the Anderson Type Anion [Xn+M6O24]-(12-n) - K. C. Dey; V. Sharma (E-Journal of Chemistry)
Sodium salts of copper substituted heteropoly compounds having molecular formula Na10[CuIIWVI6O24].22H2O(1) and Na10[CuIIMoVI6O24]. 19H2O(2) analogous to the Anderson type anion [Xn+M6O24]─(12-n) were synthesized according to the literature method. Compound(1) was synthesized from aqueous acidic solution containing sodium tungstate and copper chloride and compound(2) from sodium molybdate and copper chloride solution. The elemental analyses show 1:6 atomic ratio of the heteroatom to the addenda in both the compounds. The IR spectra for both the compounds are in good agreement with the reported formulae. A small deviation in IR spectra are observed than that established for Keggin anions. CuO6 acts as hetero group which replaces MO6 (M=W or Mo) from the Anderson structure. The thermal analyses of the compounds show the loss of the peripheral water molecules. The molecular weight of the compound (1) and (2) have been found as 2212.5 and 1600.5 respectively.